Experimental and Numerical Study on the Strength of Aluminum Extrusion Welding - Bingol, Sedat; Bozaci, Atilla (MDPI, 2015)
The quality of extrusion welding in the extruded hollow shapes is influenced significantly by the pressure and effective stress under which the material is being joined inside the welding chamber. However, extrusion welding was not accounted for in the past by the developers of finite element software packages. In this study, the strength of hollow extrusion profile with seam weld produced at different ram speeds was investigated experimentally and numerically. The experiments were performed on an extruded hollow aluminum profile which was suitable to obtain the tensile tests specimens from its seam weld's region at both parallel to extrusion direction and perpendicular to extrusion direction. A new numerical modeling approach, which was recently proposed in literature, was used for numerical analyses of the study. The simulation results performed at different ram speeds were compared with the experimental results, and a good agreement was obtained.
Keywords: extrusion; seam weld; aluminum; ram speed; FEM; simulation; PORTHOLE DIE; PREDICTION; PROFILE; HOLLOW; Chemistry; Materials Science; Metallurgy & Metallurgical Engineering; Physics